Producing wood at least cost to biodiversity: integrating Triad and sharing–sparing approaches to inform forest landscape management. (4th March 2021) - Betts, Matthew G.; Phalan, Benjamin T.; Wolf, Christopher; Baker, Susan C.; Messier, Christian; Puettmann, Klaus J.; Green, Rhys; Harris, Scott H.; Edwards, David P.; Lindenmayer, David B.; Balmford, Andrew
ABSTRACT: Forest loss and degradation are the greatest threats to biodiversity worldwide. Rising global wood demand threatens further damage to remaining native forests. Contrasting solutions across a continuum of options have been proposed, yet which of these offers most promise remains unresolved. Expansion of high‐yielding tree plantations could free up forest land for conservation provided this is implemented in tandem with stronger policies for conserving native forests. Because plantations and other intensively managed forests often support far less biodiversity than native forests, a second approach argues for widespread adoption of extensive management, or 'ecological forestry', which better simulates natural forest structure and disturbance regimes – albeit with compromised wood yields and hence a need to harvest over a larger area. A third, hybrid suggestion involves 'Triad' zoning where the landscape is divided into three sorts of management (reserve, ecological/extensive management, and intensive plantation). Progress towards resolving which of these approaches holds the most promise has been hampered by the absence of a conceptual framework and of sufficient empirical data formally to identify the most appropriate landscape‐scale proportions of reserves, extensive, and intensive management to minimize biodiversity impacts while meeting a given level of demand for wood. In this review, we argue that this central challenge for sustainable forestry is analogous to that facing food‐production systems, and that the land sharing–sparing framework devised to establish which approach to farming could meet food demand at least cost to wild species can be readily adapted to assess contrasting forest management regimes. We develop this argument in four ways: ( i ) we set out the relevance of the sharing–sparing framework for forestry and explore the degree to which concepts from agriculture can translate to a forest management context; ( ii ) we make design recommendations for empirical research on sustainable forestry to enable application of the sharing–sparing framework; ( iii ) we present overarching hypotheses which such studies could test; and ( iv ) we discuss potential pitfalls and opportunities in conceptualizing landscape management through a sharing–sparing lens. The framework we propose will enable forest managers worldwide to assess trade‐offs directly between conservation and wood production and to determine the mix of management approaches that best balances these (and other) competing objectives. The results will inform ecologically sustainable forest policy and management, reduce risks of local and global extinctions from forestry, and potentially improve a valuable sector's social license to operate.